A Model to Investigate Performance of Orthogonal Frequency Code Division Multiplexing - Nasaruddin Nasaruddin; Melinda Melinda; Ellsa Fitria Sari (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2012)
Orthogonal Frequency Code Division Multiplexing (OFCDM) is an attractive multiple access scheme for high data rate application in fourth-generation (4G) wireless communication system. Several previous researches were mainly investigated the performance of OFCDM based on variable spreading factor and subcarrier allocation. However, there are also several system parameters may affected the performance of OFCDM. For that purpose, this paper developes a model to investigate the impact of several parameters on the performance system of OFCDM over Rayleigh Fading channel as a realistic channel in wireless communication system.The proposed model is then created in the form of computer simulation using MATLAB programming in order to show the impact of several parameters for OFCDM’s performance including number of carriers, size of symbol, symbol rate, bit rate, size of guard interval and spreading factor. The simulation results show that the higher number of carriers, larger size of symbol, higher symbol rate, higher bit rate and larger spreading factor are giving the better system’s performance in terms of Bit Error Rate (BER). However, the larger guard interval is giving the worst system’s performance.So all the parameters should be considered in the implementation of OFCDM for the 4G wireless communication system.